Understanding University Students’ Learning Engagement in AI-Supported Learning Environments: An Empirical Study - Teguh Dwi Putranto; Diah Sofiah; Hetti Sari Ramadhani (Jurnal Paedagogy, 2026)
This study aims to explore university students’ lived experiences in using ChatGPT as a medium for learning engagement. A phenomenological method was employed to capture the essence of students’ experiences. The participants consisted of first-year undergraduate students from the Communication Science program at the State University of Surabaya, selected due to their transitional learning phase from secondary to higher education. Data were collected through Focus Group Discussions (FGDs). Data analysis followed a phenomenological procedure that involved transcript reading, meaning identification, thematic clustering, the development of textual and structural descriptions, and the synthesis of the essence of the phenomenon. The findings reveal that students utilize ChatGPT to answer questions, explain concepts, support writing and text editing, stimulate creativity and content production, and assist with analysis and problem-solving tasks. These findings indicate that artificial intelligence has become an integral component of the higher education learning ecosystem, necessitating a reconsideration of how student learning processes are understood. The results further suggest a shift in learning patterns—from exploratory to instant learning, from process-oriented to outcome-oriented approaches, and from independent learning to AI-assisted dependence. Excessive and uncritical use of AI may lead to a decline in students’ critical thinking, writing, analytical, and problem-solving skills. Therefore, this study recommends the cultivation of wise and reflective AI use among university students to ensure that AI serves as a supportive tool rather than a substitute for essential cognitive and metacognitive learning processes.